Work Environment, Job Stress, and Work Motivation as Determinants of Employee Performance at PT Indolakto - Sahlani Pratiwi, Theysa; Praptasari, Mutiara; Rugayah, Siti (Journal of Law and Social Politics, 2024)
Background: Work-related stress among employees can negatively affect productivity and well-being. Factors such as excessive workload, tight deadlines, and interpersonal conflicts contribute to work stress, which in turn impacts subjective, behavioral, cognitive, physiological, and health aspects, leading to decreased job satisfaction and employee performance. Objective: This study aims to analyze the influence of the work environment, work-related stress, and work motivation on employee performance at PT Indolakto. Methods: This research employed a causal research design. The population consisted of all employees of PT Indolakto, totaling 116 individuals, with a research sample of 90 employees selected for analysis. Data were collected using questionnaires measured on a Likert scale. Parametric statistical analysis was applied to examine the relationships between the independent variables—work environment, work-related stress, and work motivation—and the dependent variable, employee performance. Results: The findings indicate that the work environment, work-related stress, and work motivation have a significant influence on employee performance at PT Indolakto. A supportive work environment and high work motivation were associated with improved performance, while elevated levels of work-related stress tended to reduce employee performance. Conclusion: The study concludes that employee performance at PT Indolakto is significantly influenced by the work environment, work-related stress, and work motivation. Improving workplace conditions and managing employee stress effectively are essential strategies for enhancing employee performance and organizational outcomes.